Philosophical Foundations and Human Rights in the Bajapuik Tradition: Bridging Local Wisdom and Islamic Law in Minangkabau Marriage Practices - Jafar, Wahyu Abdul; Asmara, Musda; Faizin, Mu'adil; Octavianne, Helena; Kisworo, Budi (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This study explores the philosophical values and human rights implications within the Bajapuik tradition, a distinct matrimonial practice of the Padang Pariaman tribe in Sumatra. Explores the philosophical values of the unique amalgamation of local wisdom and Islamic law as an example of integrating cultural heritage with religious principles in marriage. As qualitative descriptive field research, data were gathered from interviews and documentation from a diverse group of informants, including religious leaders, traditional leaders, community leaders, and the people of Padang Pariaman. By utilising a sociological approach, the study examines the social realities of the Bajapuik tradition, mainly focusing on its dowry practice, particularly the maslahah (general welfare) concept. Contrary to typical dowry practices, in the Bajapuik tradition, the bride’s family provides the dowry to the groom, symbolising respect and equality rather than economic burdens. This study highlights that the Bajapuik tradition is not merely a transactional stage in the marriage process but a more profound expression of community bonds and shared values. The findings emphasise the strong philosophical values of mutual respect and companionship inherent in the Bajapuik tradition, demonstrating its alignment with Islamic law and human rights values. This research reveals how the Minangkabau’s adherence to religious and local wisdom significantly reinforces human rights within traditional practices. Furthermore, the study examines the extent to which the Bajapuik tradition achieves the objectives of maslahah in marriage. The results show that the Bajapuik tradition supports general welfare (maslahah) by strengthening social bonds, upholding the dignity of women, and ensuring justice and equality in marital relationships, offering a new perspective rarely explored in previous studies.